Organizational culture and open innovation performance in small and medium-sized enterprises (SMEs) in Poland - Jolanta Mazur; Piotr Zaborek (International Journal of Management and Economics, 2016)
This study investigates the links between organizational culture, the use of open innovation sources and the performance of SMEs. The main hypothesis of the study is that a special type of organizational culture (termed innovative culture), which fosters creativity, learning and inter-employee cooperation - will correspond with a greater scope of open innovation sources and higher levels of innovative, operational and financial performance. The study was based on a representative CATI survey of 473 SMEs operating in manufacturing and services industries in Poland. Our statistical analysis relied on building and testing structural equation model with the AMOS software. The findings confirmed a positive association between innovative culture and the scope of open sources of innovation. However, innovative culture had no direct effect on the percentage of sales from new and modified products, which is often used as a metric of innovativeness, but did show a positive influence on an index of operational performance and ROI. Such statistical patterns suggest that fostering innovative culture is beneficial to a company, though probably not through an increased number of product innovations, but rather via process, administrative and marketing innovations, as well as other gains in efficiency attained due to more streamlined employee cooperation and knowledge exchange. The study adds to the existing body of knowledge in management science by providing a better understanding of mechanisms underlying innovative culture's impacts on open innovation practices and metrics of operational and financial performance in the context of small and medium enterprises.
Keywords: M14; M54; O32; 650; organizational culture; innovative culture; open innovation; innovation performance; SMEs